The Effect of Anlotinib Combined with anti-PD-1 in the Treatment of Gastric Cancer - Zheng, Wubin; Sun, Guoqiang; Li, Zhitao; Wu, Fan; Sun, Guangshun; Cao, Hongyong; Zhou, Jin; Ma, Yong (Frontiers in Surgery, 2022)
Methods: Anlotinib was screened out of 880 drugs through Cell Counting Kit 8(CCK-8) technology. TCGA was used to detect the expression of VEGFR in GC, and Kaplan-Meier Plotter was used to analyze the correlation between the expression of VEGFR and the survival rate of GC patients. The impacts exerted by Anlotinib to GC cell proliferating, migrating and invading processes were assessed through wound healing assay, transwell assay, and proliferation assay in vitro. In vivo experiments of GC were performed in C57/B6 mouse model to evaluate the function of Anlotinib and PD1 antibody. Results: It was found from more than compunds that Anlotinib has a significant inhibitory effect on GC cells. In vitro experiments show that Anlotinib can significantly inhibit the proliferation, invasion and proliferation of GC cells. The expression level of VEGFR is related to the prognosis and survival of GC. GC patients with low expression of VEGFR have better survival. Anlotinib can inhibit the expression of PD-L1, and achieve better therapeutic effects after combined with PD1 antibody. Conclusion:The present study reveals that Anlotinib down regulates PD-L1. The combination of Anlotinib and PD-1 monoclonal antibody is beneficial to GC therapy.